Impact of underweight status on mortality in sepsis patients: a meta-analysis - Chen, Jiaan; Zhang, Fan; Liang, Li; Pan, Xuming; Zhang, Jiancheng; Jin, Guangjun (Frontiers in Medicine, 2025)
ObjectiveThe evidence regarding the impact of underweight status on clinical outcomes in patients with sepsis are still scarce and controversial. We aimed at conducting a meta-analysis to evaluate the potential associations between underweight and the mortality rate among sepsis patients.MethodsA comprehensive electronic search was performed in PubMed, Cochrane Library, Embase, and Web of Science databases. Odds ratios (ORs) or mean differences and 95% confidence intervals (CIs) were calculated using RevMan 5.3.ResultsA total of 58,348 patients (normal weight group: 49,084 patients; underweight group: 9,264 patients) from 23 studies were included in this meta-analysis. The results indicated that the in-hospital mortality (OR, 1.28; 95% CI, 1.21, 1.35; heterogeneity: I2 = 21%, P = 0.21), 28-day mortality (OR, 1.54; 95% CI, 1.26, 1.88; heterogeneity: I2 = 74%, P < 0.0001) and 1-year mortality (OR, 1.78; 95% CI, 1.58, 2.00; heterogeneity: I2 = 41%, P = 0.17) of underweight patients were significantly higher than those of normal weight patients. However, there was no significant difference in length of hospital stay or intensive care unit length of stay between underweight patients and normal-weight patients.ConclusionUnderweight is associated with increased mortality in patients with sepsis. Physicians should pay more attention to the management of underweight sepsis patients.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=631417, identifier CRD42025631417.